Faktor yang Mempengaruhi Niat Perilaku Muslim Menggunakan Platform Crowdfunding Waqf: Teori UTAUT Model - Fellasufah Diniyah (ITB AAS INDONESIA Surakarta, 2021)
This study aims to examine the determine behavioral intentions influence Muslim using platform crowdfunding waqf by adopting the concept of the Unified Theory of Accaptance and Use of Technology (UTAUT) model. The platform crowdfunding waqf acts as an intermediary between wakif and nadhir waqf in developing a productive waqf project. This study uses primary data collected using an online survey questionnaire and then the analysis used is partial least square (PLS). The results of this study indicate that the variable performance expectations, effort expectations, and facilitating conditions have a positive and significant effect on the intention of Muslim crowdfounders to use waqf crowdfunding platform. Meanwhile, the social influence variable has no positive and significant effect. This study will contribute to the existing literature, especially on the factors that influence the adoption of the waqf-based crowdfunding model.